Regional report on the achievement of the Millennium Development Goals in the Caribbean Community (UNDP New YorkUS, 2004)
Identifies broad trends in the implementation of the MDGs at the regional level highlighting in the process, the pecularities of the region. Provides a framework for assessing the approaches adopted by the different countries and identifies successful strategies that could be applied by other countries in the region. Provides a basis for cross-regional comparison.
Additional copy located in the Office of the Secretary-General